Current knowledge of echinoderms (Echinodermata) from the coast of Paraíba, northeastern Brazil - Anne Isabelley Gondim; Ellori Laíse Silva-Mota; Niviane Ferreira-Lafite; Martin Lindsey Christoffersen; Thelma Lúcia Pereira-Dias (Revista Mexicana de Biodiversidad)
The first record of echinoderms from the state of Paraíba appeared in 1789, yet the systematic survey of the phylum along the coast only began in 2008. New species and several new records have been added since. An extensive literature survey and an analysis of the main Echinodermata collections housed in Brazil yielded 74 species. Our qualitative survey results in up-to-date records of echinoderm species along the littoral of the state, including information on habitat and their occurrence in Conservation Units (UCs). Even though all records are from the intertidal to 35 m, the resulting diversity of species is high when compared to other areas, since it corresponds to 21% of all Brazilian species and to 16% of the species known from the Caribbean Sea. The main habitats used by echinoderms are reefs and rhodolith beds. About 15% of the species are in the Brazilian Red List. A positive result is that 67% of these species occur within UCs in the state. Based on these results, we conclude that the fauna of echinoderms from shallow water is well documented in Paraíba. Finally, we comment on the conservation status of species and indicate future directions for the study of Echinodermata.